2006
DOI: 10.1063/1.2174012
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic NMR spectroscopy of endohedral hydrogen-fullerene complexes

Abstract: We have observed 1H NMR spectra of hydrogen molecules trapped inside modified fullerene cages under cryogenic conditions. Experiments on static samples were performed at sample temperatures down to 4.3 K, while magic-angle-spinning (MAS) experiments were performed at temperatures down to 20 K at spinning frequencies of 15 kHz. Both types of NMR spectra show a large increase in the intramolecular 1H-1H dipolar coupling at temperatures below 50 K, revealing thermal selection of a small number of spatial rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
84
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 33 publications
4
84
0
Order By: Relevance
“…Applying Refs. [11,12] it may be shown that, the fullerene cage has been estimated previously from the molecular structure [7] and to a first approximation the H 2 molecule occupies a sphere with root mean square radius (rms), Therefore, although in this provisional analysis the cage has been approximated with spherical shape, a very consistent picture has emerged, confirming the assignments to the rotational and translation manifolds. In fact the translational band has structure and is best fitted as a doublet with energies 17.10 and 17.90meV.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Applying Refs. [11,12] it may be shown that, the fullerene cage has been estimated previously from the molecular structure [7] and to a first approximation the H 2 molecule occupies a sphere with root mean square radius (rms), Therefore, although in this provisional analysis the cage has been approximated with spherical shape, a very consistent picture has emerged, confirming the assignments to the rotational and translation manifolds. In fact the translational band has structure and is best fitted as a doublet with energies 17.10 and 17.90meV.…”
mentioning
confidence: 60%
“…In spherical symmetry the first excited translational state is three-fold degenerate but in the presence of an anisotropic cage this degeneracy is fully lifted. In this case the translational states are described by three quantum numbers One axis of the ATOCF cage is significantly narrower than the other two with an effective radius estimated to be 0.60Å compared with a rms radius of 0.78Å for the cage as a whole [7]. Scaling the observed translations at ≈17.5meV by the …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent IR spectroscopic studies of H 2 @C 60 [4] as well as of endohedral HD and D 2 in C 60 [7] have provided a great deal of valuable information about the T-R energy levels of the guest molecules and their interaction potentials with C 60 . The physical properties of hydrogen endofullerenes have also been probed by nuclear magnetic resonance [1,8,9]. What has enabled the experimental investigations is the synthetic organic breakthrough, known as 'molecular surgery', by Komatsu and co-workers [10,11] for producing macroscopic amounts of H 2 @C 60 and HD@C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…But, much more detailed and sophisticated studies on the NMR of this molecule have been conducted by the group of Levitt and co-workers [7]. The molecular hydrogen inside the fullerene cage gives us a good opportunity to study its spin chemistry and physics, as well as NMR, which have been carried out actively by the group of Turro and co-workers [8].…”
mentioning
confidence: 99%